BRIDGING THE SUPPLY AND DEMAND GAP FOR AFFORDABLE HOME OWNERSHIP IN MALAYSIA: THE ROLES OF GOVERNMENT AND FINANCIAL INSTITUTIONS - Mohd Yusof, Rosylin; Mohd Khan, Shazida Jan; M. Yusuf, Fauziah; Abdul Majid, Nurul Huda (PLANNING MALAYSIA, 2019)
Promoting homeownership remains a conundrum in a developing economy in Malaysia. Despite significant initiatives pursued by the government, more needs to be done to promote affordable and sustainable homeownership further. Khazanah Report (2018) provides evidence that housing affordability in Malaysia is worsening compared to one reported in 2015.This study therefore aims to empirically assess the role of government in terms of designing policies to promote the supply of affordable homes and the role of financial institutions in terms of providing home financing. The finding reveals that existing housing policies and government programmes have a significant role in promoting homeownership. The finding further suggests that building and completing more units of affordable homes (as captured by housing stocks) and promoting innovative home financing products (both conventional and Islamic) are the most significant variables in promoting homeownership in Malaysia.